Tentera darat menentang insurgensi komunis 1968-1989 - Malaysia. Tentera Darat (Kuala Lumpur : Markas Tentera Darat, 2001)
Role of Malaysian Army in fighting communism between 1968 - 1989
In Malay
Includes bibliographical references (p. 218-219)
Keywords: Insurgency -- Malaysia -- History; Communism -- Malaysia -- History; Malaysia -- History